IMPROVING THE SCIENTIFIC-THEORETICAL BASIS OF PRIMARY EDUCATION TEACHER TRAINING - Rakhimova Dilnoza Anvarjonovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article is about improving the scientific-theoretical basis of training primary education teachers for the young generation to grow up physically and mentally.